A High‐Energy Aqueous Aluminum‐Manganese Battery. (2nd September 2019) - He, Shiman; Wang, Jie; Zhang, Xu; Chen, Jingzhao; Wang, Zichun; Yang, Tingting; Liu, Zhiwei; Liang, Yuan; Wang, Boya; Liu, Shiqi; Zhang, Liqiang; Huang, Jianyu; et al.
Abstract: Rechargeable aluminum‐ion batteries have drawn considerable attention as a new energy storage system, but their applications are still significantly impeded by critical issues such as low energy density and the lack of excellent electrolytes. Herein, a high‐energy aluminum‐manganese battery is fabricated by using a Birnessite MnO2 cathode, which can be greatly optimized by a divalence manganese ions (Mn 2+ ) electrolyte pre‐addition strategy. The battery exhibits a remarkable energy density of 620 Wh kg −1 (based on the Birnessite MnO2 material) and a capacity retention above 320 mAh g −1 for over 65 cycles, much superior to that with no Mn 2+ pre‐addition. The electrochemical reactions of the battery are scrutinized by a series of analysis techniques, indicating that the Birnessite MnO2 pristine cathode is first reduced as Mn 2+ to dissolve in the electrolyte upon discharge, and Al x Mn(1− x ) O2 is then generated upon charge, serving as a reversible cathode active material in following cycles. This work provides new opportunities for the development of high‐performance and low‐cost aqueous aluminum‐ion batteries for prospective applications. Abstract : A high‐energy aluminum‐manganese battery is developed by using a Birnessite MnO2 ( Bir ‐MnO2 ) pristine cathode, which can be greatly optimized by a Mn 2+ electrolyte pre‐addition strategy. With the reversible deposition/dissolution of Mn 2+ /Al x Mn(1− x ) O2, the battery exhibits a remarkable capacity of 554 mAh g −1, corresponding to an energy density of ≈620 Wh kg −1 (based on the Bir ‐MnO2 material), and a good cycling stability.